2020
DOI: 10.1055/s-0040-1721738
|View full text |Cite
|
Sign up to set email alerts
|

Inborn Errors of Metabolism in a Tertiary Pediatric Intensive Care Unit

Abstract: Few studies exist describing resources and care of pediatric patients with inborn errors of metabolism (IEM) admitted to pediatric intensive care unit (PICU). This study aims to characterize the PICU admissions of these patients to provide better diagnostic and therapeutic care in the future. Retrospective analysis of pediatric patients with IEM admitted to the PICU of a tertiary care center at a metabolic referral university hospital from 2009 to 2019 was included. Clinical information and demographic data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…There were 8 deaths in this group of patients. 4 Results similar to these were also described by Couce et al, who observed 31 cases of patients with IEM out of 1,104 admissions to the pediatric ward over an 8-year period, accounting for 1.63% of all hospitalizations. Of these cases, 18 required intensive care, and 12 patients had a clinical picture of acute encephalopathy that did not require ICU care.…”
Section: Metabolic Encephalopathy: Definition and Scale Of The Problemsupporting
confidence: 84%
See 2 more Smart Citations
“…There were 8 deaths in this group of patients. 4 Results similar to these were also described by Couce et al, who observed 31 cases of patients with IEM out of 1,104 admissions to the pediatric ward over an 8-year period, accounting for 1.63% of all hospitalizations. Of these cases, 18 required intensive care, and 12 patients had a clinical picture of acute encephalopathy that did not require ICU care.…”
Section: Metabolic Encephalopathy: Definition and Scale Of The Problemsupporting
confidence: 84%
“…In a study by Lipari et al, the numbers of patients admitted were 23 and 21, respectively, out of 65 hospitalized for encephalopathy. 4 Similar proportions of patients with IG and EFG are reported in other studies: 5 and 6 out of 11 hospitalized with IEM, respectively 6 and 5 and 4 out of 10 hospitalized with IEM. 1…”
Section: Metabolic Encephalopathy: Definition and Scale Of The Problemsupporting
confidence: 80%
See 1 more Smart Citation
“…Authors did a commendable job in highlighting the intensive care course and outcome of children with IEMs. 1 We would like to highlight few points pertinent to our setting. In developing countries like India, there is lack of universal neonatal testing for IEMs.…”
mentioning
confidence: 99%
“…We read with interest the recently published article titled "Inborn Errors of Metabolism in a Tertiary Pediatric Intensive Care Unit" by Lipari et al 1 and want to make few important comments. Authors enrolled 65 cases of inborn errors of metabolism (IEMs) with 88 admission to a pediatric intensive care unit (PICU) in Portugal over a period 11 years (2009-2019) accounting for 2% of PICU admissions.…”
mentioning
confidence: 99%